PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN Usaha Dagang - Rizky Oktavian, Ade (PT Kimshafi Alung Cipta, 2022)
This research was motivated by the low performance of employees of the Trading Business in Central Java. The problem in this study is the dominant variables in influencing the performance of Trading Business employees including transformational leadership style, organizational culture and motivation